(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The current process of reforms in the cultural and educational spheres also poses a number of new tasks for Uzbek literary studies. “Today, we are moving towards the path of innovative development aimed at radically renewing all spheres of state and social life. This is not without reason, of course. Because in the current era, when time is developing rapidly, who will win? The state that relies on new thoughts, new ideas, and innovations will win”.